Conflict analysis of community rejection and acceptance of PT Geo DIPA Energi’s Dieng geothermal working area - Sulastri, Heni; Wijaya, Andy Fefta; Saleh, Choirul; Hermawan, Hermawan; Haikal, Haikal (Edelweiss Applied Science and Technology, 2025)
The discourse surrounding community acceptance and rejection of PT Geo Dipa Energi’s geothermal working area project in Dieng is a significant topic within the sociology of conflict studies. In Indonesia, the development of geothermal working areas offers economic and infrastructural benefits; however, for some communities, the project raises environmental and health concerns. This research aims to examine and analyze the discourse of acceptance and rejection by applying social conflict theory to understand the differences in community responses to the project. It employs a qualitative approach with the symbolic interactionism method to understand how the meanings of acceptance and rejection are formed through social interactions. Data were collected through in-depth interviews, observations, and documentation from communities in several villages around the Dieng PLTP. The results indicate that conflicts related to the Dieng PLTP project reflect a clash between economic interests pursued by companies and the government and the social-ecological interests of local communities, who feel threatened by environmental impacts.